Ocean observation system design of mooring buoy and benthic node with electro-optical-mechanical cable - Zhang, Shaowei; Tian, Chuan; Zhou, Fenghua (Frontiers in Marine Science, 2022)
We designed a hybrid system named Mooring Buoys Observation System with Benthic Electro-optical-mechanical Cable (MBOSBC) for long-term seafloor and sea surface multi-parameter ocean observation. The electro-optical-mechanical (EOM) cable connects a sea surface buoy and a seafloor junction box so as to establish a transmission link of information and power between the sea surface and the seafloor. The EOM cable also plays the role of mooring tether to the MBOSBC and has to withstand the rigorous marine environment—experiencing mooring loads under complex marine environmental conditions for long periods of time. The data transmission of the system includes the EOM, satellite communication, wireless radio, and acoustic communication. The system power is generated by a wind turbine and solar panels and is transmitted to the seafloor junction box. An acoustic communication instrument is used to gather the sample data from other benthic nodes, such as seafloor landers, AUVs, and underwater gliders. MBOSBC is designed to operate from shallow water to deep sea, and to simultaneously monitor sea surface hydrology, meteorology, and water quality, as well as benthic temperature, pressure, salinity, currents, and seafloor video. We provide the MBOSBC architecture design, including the mechanical design, control, power, data transmission, and EOM cable. Finally, we describe the launch and recovery process of MBOSBC, as well as experimental results.